The Effect of Servant Leadership and Breakthrough Leadership on Organization Performance with Employee Satisfaction as Intervening Variable at IDX-listed (Indonesia Stock Exchange) Coal Mining Companies in Indonesia - Triraharjo, Joko; Aima, Havidz; Sutawijaya, Achmad (International Review of Management and Marketing, 2019)
Indonesia is the third largest coal producer in the world. Indonesia's total coal production in 2018 is 528 million tons. Of this amount, 320 million tons are produced by coal mining companies listed on the Indonesia Stock Exchange. Among these coal mining companies, there are large performance gaps between each other, both in terms of financial performance and production achievement. Their performance is hypothesized to be influenced by leadership style. The purpose of this study was to analyze the influence of servant leadership and breakthrough leadership on organizational performance with employee satisfaction as an intervening variable in coal mining companies listed on the Indonesia Stock Exchange. Respondents from this study were 12 coal mining companies listed on the IDX in Indonesia. The type of research used is quantitative methods. The research respondents were 113 people in the position of supervisors to directors. Data were analyzed using the Structural Equation Model (SEM - AMOS). The results showed that servant leadership did not have a positive impact on employee satisfaction but had a positive impact on organizational performance, while Breakthrough Leadership had a positive impact on employee satisfaction but did not have a positive impact on organizational performance. Employee satisfaction has a positive and significant impact on organizational performance but does not mediate organizational performance. Novelty from this research is about breakthrough leadership. Keywords: Servant Leadership, Breakthrough Leadership, Employee Satisfaction, Organizational Performance. JEL Classifications: L1, L2 DOI: https://doi.org/10.32479/irmm.8159